(untitled) (Revista de Ciências Agroveterinárias, 2016)
Injuries in the internal structures of the seeds limit their viability and can reduce their vigor, producing weak seedlings susceptible to adverse conditions. Thus, the determination of the quality of seeds of Physalis peruviana L. by X-ray test is valid, in order to reduce the time separation of seeds and a good initial establishment of the culture. Considering the above, the objective of the present study was to evaluate the quality of physalis seeds at different stages of development of fruit by X-ray test. The seeds were removed and separated into lots according to the fruit maturation stage, being fruits with intermediate maturity (50% of the ripe fruit), completely ripe fruits and completely ripe fruits subjected to seven days of rest after harvest. Posteriorly they were subjected to X-rays for determination of seed quality. The experimental design consisted of eight replicates of one hundred seeds per lot. Physalis fruit seeds with 50% maturation have lower morphophysiological quality when compared to seeds extracted from completely ripe fruits. Seed vigor is greater when the fruits are subjected to rest for seven days. The X-ray test is efficient for selection of non-viable seed of physalis.